The Understanding and Behavior of Fishermen toward the Social Security Program Case Study; the Fishermen in the District ofKaur, Bengkulu - saptia, yeni (Badan kebijakan Fiskal, 2013)
The social security program is expected to help reducing the risk of fishermen. This study aims to analyze the understanding, intention and behavior of fishermen on the social security program. Sample of respondents of this study amounted to 116 fishermen in the District ofKaur who have under 10 GT dimension of ship. The analytical method is used a Structural Equation Model (SEM) that adopts the Ajzen's theory of planned behavior by using the Amos 19. The results of the study showed that the positive response of fishermen on the social security program as well as the subjective norm ofKaur Fishermen effect directly the intention and indirectly the behavior of fishermen to pay the dues of social security program. While the behavior control of fishermen in Kaur is not significant in influencing the intention and behavior of the social security program.